DAMPAK STRES AKADEMIK SISWA DALAM MENENTUKAN PERENCANAAN KARIER DI SMA - Dyah Pitaloka Putri Dewi; Nurmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to describe the forms of academic stress experienced by students, examine students’ career planning, and analyze the impact of academic stress on career planning among students at SMA Islam PB Soedirman Jakarta. The study employed a qualitative approach with a descriptive research design. The participants were Grade XI students identified as experiencing academic stress based on counseling assessment results and supported by information from guidance and counseling teachers as well as subject teachers. Data were collected through observation, in-depth interviews, and documentation. Data analysis was conducted using the Miles and Huberman model, which includes data condensation, data display, and conclusion drawing and verification. The findings revealed that students experienced academic stress due to several factors, including heavy academic workloads, an accelerated curriculum system, demands for high academic achievement, academic competition, and expectations from parents and the school environment. Academic stress was reflected in physical reactions such as fatigue and sleep disturbances, emotional reactions such as anxiety and emotional instability, and cognitive reactions such as difficulty concentrating and self-doubt. These conditions affected students’ career planning, particularly in career exploration, career information seeking, decision-making, and confidence in career choices. As a result, students tended to experience confusion in determining future educational pathways and career directions. The study concludes that academic stress can hinder the development of mature career planning. Therefore, guidance and counseling services play an important role in helping students manage academic stress, enhance self-understanding, and develop more mature, independent, and realistic career plans. Keywords: academic stress, career planning, guidance and counseling